SEGREGASI PADA ELEMEN-ELEMEN PERKOTAAN ANTARA PERUMAHAN-PERUMAHAN FORMAL DAN KAMPUNG PONDOK JENGKOL, TANGERANG - Wibowo, Vivian Dea; Khamdevi, Muhammar (ALUR :Jurnal Arsitektur, 2025)
Segregation between formal housing and existing villages can be found in new town areas in Indonesia, such as the differences in planning and design in BSD and Gading Serpong new towns and the surrounding village areas in Tangerang, Banten. This phenomenon is evident in places like Pondok Jengkol Village. The contrasting planning and design between BSD City and Gading Serpong and Kampung Pondok Jengkol result in minimal regional continuity and lack of harmony between the areas. This research aims to identify segregation on urban elements in existing village and new town development areas. The study employs descriptive qualitative research methods by analyzing existing data through case studies. The results indicate spatial segregation on land use element and physical segregation on building mass form, circulation and parking, open space, pedestrian areas, activity support, signage, and preservation elements between village and formal settlements.